Ruins of sacred buildings: ideological message and problems of its preservation - Piotr Krasny (Ochrona Dziedzictwa Kulturowego, 2020)
The ruin is a building, whose shape is deformed and decoration have suffered significant loses. So the viewer’s attention is attracted by the ideological message of ruins, which is always different from the set of meanings of the complete edifice, and often contradicts it. This is clearly seen in the case of sacred buildings. In the 16th and 17th centuries Roman Catholic writers claimed, that the ruins of pagan temples in Rome are monuments of the ancient Roman Empire’s power, but their current state clearly shows the defeat of paganism and triumph of Christianity. The prelates thought that it was necessary to take care of the ruins, but they should not be rebuilt. Protestant writers in the British Isles took a similar attitude to the local ruins of monastic temples, seeing in them a clear manifestation of the fall of the “papist religion” and the triumph of Protestantism. During the French Revolution, remains of the ruined churches were consciously preserved as monuments of the decline of Christianity and the triumph of the new cult of reason. So rejection of the religion granted protection to ruins of sacred buildings. However the religious indifference growing in many communities causes problems with determining the place of such ruins in public space. Reducing them to the role of bizarre "street furniture" (eg the church of Saint-Livier in Metz), causes their ideological neglection, often contributes to their material destruction. Preventing such situation seems to be an important challenge for conservators dealing with the problem of "permanent ruin".